Secondary renocolic fistula caused by pyonephrosis - Prelević, Rade; Milev, Boško; Ignjatović, Mihajlo; Jovanović, Mirko; Prelević, Danilo (Vojnosanitetski pregled, 2021)
Introduction. Renoalimentary fistulas represent infrequent pathology with 27 literature reports. The oldest report is from the year 1953. Nowadays, they usually arise after the cryoablation of renal tumors. In this case, we reported secondary renocolic fistula as an unusual complication of pyonephrosis, as well as the treatment modality, providing a literature review that favors a conservative or minimally invasive approach in most cases of renocolic fistula. Case report. In our case, the patient was a young female with a long course of kidney disease, which eventually led to pyonephrosis with renocolic fistula. Initially, the patient was hospitalized due to life-threatening urosepsis, successfully treated with a conservative approach. Afterward, we decided to proceed with surgical treatment. Regarding the poor right kidney function of the patient and the presence of concurrent sepsis, the right hemicolectomy with primary ileocolic anastomosis and the right nephrectomy were performed. The postoperative course was without complications, and the patient was discharged from the hospital on the 10th day. Follow-up did not reveal any complications. Conclusion. Regarding the available literature, a conservative and minimally invasive approach is most frequently employed in such cases. However, in cases of haemorrhage, sepsis, and impaired kidney function, surgery offers the only chance for cure. In patients with concurrent gastrointestinal pathology, surgery is usually the only option. Kidney preservation should be imperative in all cases, except in the case of impaired kidney function. The laparoscopic approach can be utilized in selected cases.